Profitabilitas, Leverage, Kepemilikan Manajemen, dan Pengungkapan Corporate Social Responsibility - Maharani, Ni Luh Ari; Sudana, I Putu (E-Jurnal Akuntansi; Vol 33 No 11 (2023)DO - 10.24843/EJA.2023.v33.i11.p19, 2023)
Disclosure of corporate social responsibility is reporting information to stakeholders about company activities regarding social and environmental responsibility. The research is aimed at obtaining empirical studies regarding the influence of profitability, leverage and management ownership on CSR disclosure. This research uses 188 observations from energy sector companies listed on the Indonesia Stock Exchange in 2018-2021. Data were analyzed using multiple linear regression analysis. The results of the analysis show that profitability, leverage and management ownership have a positive effect on CSR disclosure. This implies that stakeholder theory is able to underlie the study of CSR disclosures. Keywords: Stakeholder Theory; Disclosure; Corporate Social Responsibility